Teaching representations on Information and Communication Technologies (ICT) for the teaching of psychology - Covarrubias Papahiu, Patricia del Carmen (2020)
The adoption of Information and Communication Technologies (ICTs) in education has changed the ways of communicating and building knowledge and produced new teaching and learning environments in recent years, but although they have been an indispensable component of curricular innovation, they have not had the expected impact on improving education. In this sense, the purpose of the research reported was to investigate the representations and meanings that teachers who participate in processes of teaching and learning psychology hold about ICTs and the experience they have in using them in their teaching practice. A descriptive and interpretative type of research was carried out based on a qualitative methodology, in which a semi-structured interview was applied to teachers who teach psychology contents in higher education institutions, both public and private, in the metropolitan area of Mexico. The results show that the teachers interviewed, in general, conceive ICTs as innovative and unavoidable for educational practice; nevertheless, and although they assign different meanings to them, they agree that they should be used with certain restrictions. Although pragmatic and instrumental use prevails among teachers, they believe that ICTs facilitate teaching and learning processes.